The difference quotient and simplification will be = [4 -h-2x]
The given equation is as follows: f(x)= 4x - x²
For finding the quotient and further simplification we must follow the following steps:
[f(x + h) - f(x)] / h = [4(x + h) - (x + h)² - 4x + x²]/ h
<h3>What is simplification of algebraic operations?</h3>
Getting the functions in their lowest terms is known as simplification.
Brackets will get open and solved further;
[f(x + h) - f(x)] / h = [4(x + h) - (x + h)² - 4x + x²]/ h
[f(x + h) - f(x)] / h = [4h - h² - 2x]/ h
Finally dividing the whole equation with h;
= [4 - h - 2x]
Learn more about algebraic operations,
brainly.com/question/12485460
# SPJ1
To find the inverse all you do is swap your x and y then solve it through. for this one you gotta take f(x) and make it y
y = 1/4x - 12
then swap
x = 1/4y - 12
then solve it through
x - 12 = 1/4y
divide by (1/4)
and (x - 12)4 = y should be your answer
Answer: the 2nd and the 5th one
Step-by-step explanation: